Enhanced Skeletal Muscle Oxidative Capacity and Capillary-to-Fiber Ratio Following Moderately Increased Testosterone Exposure in Young Healthy Women - Cardinale, Daniele A.; Horwath, Oscar; Elings-Knutsson, Jona; Helge, Torbjörn; Godhe, Manne; Bermon, Stéphane; Moberg, Marcus; Flockhart, Mikael; Larsen, Filip J.; Hirschberg, Angelica Lindén; Ekblom, Björn (Frontiers in Physiology, 2020)
Background: Recently, it was shown that exogenously administered testosterone enhances endurance capacity in women. In this study, our understanding on the effects of exogenous testosterone on key determinants of oxygen transport and utilisation in skeletal muscle is expanded. Methods: In a double-blinded, randomised, placebo-controlled trial, 48 healthy active women were randomised to 10 weeks of daily application of 10 mg of testosterone cream or placebo. Before and after the intervention, VO2 max, body composition, total haemoglobin (Hb) mass and blood volumes were assessed. Biopsies from the vastus lateralis muscle were obtained before and after the intervention to assess mitochondrial protein abundance, capillary density, capillary-to-fibre ratio and skeletal muscle oxidative capacity. Results: Oxygen consumption per lean muscle mass, Hb mass, blood, plasma and red blood cell volumes, capillary density and the abundance of mitochondrial protein levels (i.e.., citrate synthase, complexes I, II, III, IV-subunit 2, IV-subunit 4 and V) were unchanged by the intervention. However, the capillary-to-fibre ratio, specific mitochondrial respiratory flux activating complex I and linked complex I and II, uncoupled respiration and electron transport system capacity, but not leak respiration or fat respiration, were significantly increased following testosterone administration compared to placebo. Conclusions: This study provides novel insights into physiological actions of increased testosterone exposure on key determinants of oxygen diffusion and utilisation in skeletal muscle of women. Our findings show that higher skeletal muscle oxidative capacity coupled to higher capillary-to-fibre ratio could be major contributing factors that improve endurance performance following moderately increased testosterone exposure.